Cluster Of Differentiation 4 (CD4) dapat Mencegah Peningkatan Stadium Klinis Pasien HIV/AIDS: Kajian Pustaka - Della Desliana; Wida Purbaningsih; Umar Islami (UNISBA Press, 2022)
Abstract. Acquired immunodeficiency syndrome (AIDS) is a disease caused by the Human Immunodeficiency Virus (HIV) which attacks the human immune system. HIV/AIDS continues to grow and increase throughout the world. HIV infection can cause immunosuppression in HIV/AIDS patients which will then play a role in worsening manifestations and increasing clinical stage according to WHO. Opportunistic infections will be more prone to occur in patients with a high clinical stage, the condition can eventually be life-threatening. The frequency of opportunistic infections is strongly influenced by genetics, environment and social background. There are several factors that affect CD4 levels and clinical stage, one of which is age, antiretroviral therapy (ART) and syphilis infection. Abstrak. Acquired immunodeficiency syndrome (AIDS) adalah suatu penyakit yang disebabkan oleh Human immunodeficiency virus (HIV) yang menyerang sistem imun pada manusia. Penyakit HIV/AIDS semakin terus berkembang dan meningkat di seluruh dunia. Infeksi HIV dapat menyebabkan terjadinya imunosupresi pada pasien HIV/AIDS yang kemudian akan berperan dalam perburukan manifestasi dan peningkatan stadium klinis berdasarkan WHO. Infeksi oportunistik akan lebih rentan terjadi pada pasien dengan stadium klinis yang tinggi, kondisi tersebut pada akhirnya dapat mengancam jiwa. Frekuensi infeksi oportunistik sangat dipengaruhi oleh genetik, lingkungan dan latar belakang sosial. Terdapat beberapa faktor yang memengaruhi kadar CD4 dan stadium klinis salah satunya adalah usia, terapi antiretroviral (ART) dan infeksi sifilis.